Highlights of the AAP world wire at 14: 00 March 20 (AAP General News Wire, 2016)
MILAN/TRIPOLI, March 19 Reuters - Italy's coast guard says it has rescued more than 900 migrants in four separate operations in the Strait of Sicily, while Libyan authorities say they have rescued nearly 600 migrants from four boats. (MIGRANTS EUROPE) LONDON, March 20 AP - While the rest of her subjects call the Queen "Your Majesty", her great-grandson knows her as "Gan-Gan". (ROYALS QUEEN (pics available)) LONDON, March 20 PA - Doctors believe a "revolutionary" sound wave technique being used to treat prostate cancer could be as effective as surgery or radiotherapy - and cause fewer side effects. (MED PROSTATE)